Constructing comparisons: Reflecting on the experimental nature of new comparative tactics. (June 2022) - Brill, Frances
In this commentary I reflect on experimental approaches to comparative urbanism emerging in recent papers. Drawing on the methodological approaches employed in the special issue on Comparative Methods for Global Urban Studies, I highlight the way in which a more reactive and responsive approach – to both pre-existing conditions and understandings of urban development, as well as realities faced during fieldwork and analysis – have elucidated new ways of thinking with and through different cities to productively push forward the comparative urbanism agenda. In doing so I build on the long history of comparative approaches in urban studies to argue that experimenting with how we put new places into existing conversations, within a particular project or beyond, can be hugely powerful in transforming the way in which comparison is conducted in urban studies and geography.